Vulnerable Plaque in Patients with Acute Coronary Syndrome: Identification, Importance, and Management - Atsushi Sakamoto; Anne Cornelissen; Yu Sato; Masayuki Mori; Rika Kawakami; Kenji Kawai; Saikat Kumar B Ghosh; Weili Xu; Biniyam G Abebe; Armelle Dikongue; Frank D Kolodgie; Renu Virmani; et al. (US Cardiology Review)
MI is a leading cause of morbidity and mortality worldwide. Coronary artery thrombosis is the final pathologic feature of the most cases of acute MI primarily caused by atherosclerotic coronary artery disease. The concept of vulnerable plaque has evolved over the years but originated from early pioneering work unveiling the crucial role of plaque rupture and subsequent coronary thrombosis as the dominant cause of MI. Along with systemic cardiovascular risk factors, developments of intravascular and non-invasive imaging modalities have allowed us to identify coronary plaques thought to be at high risk for rupture. However, morphological features alone may only be one of many factors which promote plaque progression. The current vulnerable-plaque-oriented approaches to accomplish personalized risk assessment and treatment have significant room for improvement. In this review, the authors discuss recent advances in the understanding of vulnerable plaque and its management strategy from pathology and clinical perspectives.